The leadership and supervisory practices of principals in public secondary schools of the State of Amhara, Ethiopia, as perceived by teachers - Melaku Mengistu Gebremeskel; Demeke Wolie Ambaye (College of education, Bahir Dar University, 2023)
This study aimed at examining the leadership and supervisory practices of secondary school principals in the State of Amhara in view of teachers. It investigated the leadership factors that attributed for poor education quality. To that effect, the leadership and supervisory practices of principals were examined. The study employed the descriptive survey research design of the quantitative approach involving 1115 teachers recruited through a proportionate stratified random sampling technique. Data collected through a questionnaire and analyzed using descriptive statistics and multivariate analyses of variance revealed that teachers perceived the leadership and supervisory practices of principals were weak. Teachers have very weak differences in terms of three demographic factors, except sex which has no difference at all, regarding their poor leadership practices. Regarding supervisory practices, qualification level demonstrated a weak difference, the rest three with no significant differences. In addition, teachers' acknowledgment of the supervisory role of their principals is inversely correlated to the qualification level former, despite the weak difference. That is, the higher teachers' qualification level the less they acknowledge the supervisory role of their principals. The findings also revealed that leadership and supervisory practices of principals are correlated positively and significantly. Such a perception may have far-reaching consequences on the commitment and effectiveness of teachers and the quality of education. Therefore, the assignment of principals needs to be based on competence to foster commitment and ownership among all parties. In addition, further research that triangulates data from students, principals, and other stakeholders through different methods shall be conducted to resolve leadership-related limitations in secondary schools.